Hubungan Ketercapaian Kadar Gula Darah Dengan Aturan Pakai Obat Gula Darah Pada Pasien Diabetes Dengan Hipertensi - Murdiana, Happy Elda; Mediastuti, Fitriani; Rosita , Melia Eka; Suwarni, Sri (Jurnal Farmasi & Sains Indonesia, 2023)
Diabetes mellitus (DM) is a chronic metabolic disease that causes death in the world. The government’s effort to help patients with DM slow down to meet complications with the integrated health service system, namely Prolanis. This study aims to determine the relationship between the achievement of ideal blood glucose levels with the accuracy of the rules for using Antidiabetic Oral (ADO), and compliance with coming to health facilities, as well as the relationship between achieving ideal blood pressure with the accuracy of rules for using antihypertension drug and compliance with coming to health facilities. The research was conducted at the Darmarini Public Health Center, Temanggung with the research subject of DM patients with comorbid hypertension, the number of prolanis participants was 47 people. Data processing is analyzed by chi-square. There is a relationship if p<0,05 and expected count >5. This study showed that there was a significant relationship between the achievement of ideal blood glucose levels with the rules for using ADO, but there was no relationship between the achievement of ideal blood glucose levels with compliance with visits to health facilities, achieving ideal blood pressure level with the accuracy of the rules of use and compliance with visits to health facilities